2017
DOI: 10.1007/s13197-016-2479-2
|View full text |Cite
|
Sign up to set email alerts
|

A comparative overview of antioxidative properties and phenolic profiles of different fungal origins: fruiting bodies and submerged cultures of Coprinus comatus and Coprinellus truncorum

Abstract: Bioactive properties of fungi considerably differ between the fruiting body (FB) and the submerged culture as regards mycelia (M) and the fermentation broth (F). Antioxidant properties of hot-water extracts obtained from three different fungal origins: FB, M and F of two autochthonous fungal species (Northern Serbia), Coprinus comatus and Coprinellus truncorum were investigated. Free radical scavenging capacity (RSC) was evaluated in vitro by the DPPH assay and reducing power ability (FRAP assay). Considering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 36 publications
1
30
0
3
Order By: Relevance
“…Generally speaking, it is believed that phenolics are primarily responsible for AO [1,5,6]. These compounds may originate either from fruiting bodies (generative structures) or from mycelia and extracellular broth (i.e., from the filtrate of a submerged culture, vegetative structures) [7]. Submerged cultivation of macrofungi represents a biotechnological process for their growth under controlled conditions aiming to provide valuable biomass and extracellular metabolites [8].…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, it is believed that phenolics are primarily responsible for AO [1,5,6]. These compounds may originate either from fruiting bodies (generative structures) or from mycelia and extracellular broth (i.e., from the filtrate of a submerged culture, vegetative structures) [7]. Submerged cultivation of macrofungi represents a biotechnological process for their growth under controlled conditions aiming to provide valuable biomass and extracellular metabolites [8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been confirmed that mushroom extracts are a promising source of natural phenolic and flavonoid compounds [42][43][44][45]. Hot water extracts of medicinal mushrooms can be a source of bioactive flavonoids that could not be isolated at lower temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…[40], it seems that water extraction is suitable for this type of phenolic acids. So, diluting methanol with water provided a higher concentration of quinic acid in the extract of our C. comatus, though not as high as in the previously mentioned study of Tešanovićet al [40]. With respect to flavonoids, there are contradictory data in the literature.…”
Section: Phenolic Profilementioning
confidence: 99%